Beyond Borders: Myotonic Dystrophies - A European Perception - Benedikt Schoser (Frontiers Research Topics, 2019)
Myotonic dystrophies (DMs) are pleotropic multisystemic diseases. These dominantly transmitted repeat disorders affect multiple organs of the human body at all ages - from the newborns to the elderly. The present Research Topic represents a timely addition to the expanding body of evidence which aims to provide novel perspectives in our understanding of myotonic dystrophies. This collection of original contributions and standpoint reviews from multiple leading DM centres in Europe describes the state of the art for the characterization of the DMs diseases, the development of molecular strategies to target its multisystemic nature, and provides evidence of screening and testing novel therapeutic avenues.